Psychometric Properties of a Multidimensional Scale of Sense of Community in the School - Prati, Gabriele; Cicognani, Elvira; Albanesi, Cinzia (Frontiers in Psychology, 2017)
Sense of community in the school has been associated with a range of important outcomes for students. However, there are currently no standard definitions of sense of community in the school with corresponding measures with established psychometric properties. To fill this gap, the main aim of the present study was to propose a model of sense of community in the school, its operationalization and to examine its key psychometric properties (factorial structure, reliability, differential item functioning, differential test functioning of the scale and discriminant, convergent, and criterion validity). Participants were 1,076 students from 22 public middle schools and 724 students from 22 public high schools located in the Italian city of Genoa and its province. To test the dimensionality of the scale, we conducted exploratory and confirmatory factor analysis under the Item Response Theory paradigm. Exploratory factor analysis confirmed three dimensions: Membership, Emotional connection, and Opportunities. A confirmatory factor analysis revealed that the bifactor model exhibited the largest improvement in fit. Cronbach’s alpha, omega total, and omega hierarchical indicated a good reliability for the measure. Internal consistency was satisfactory, considering Cronbach’s alpha and omega. Analysis of differential item/test functioning of the scale showed that girls and boys as well as students attending middle school and those attending high school responded in largely similar ways to the measure. Finally, the instrument demonstrated good discriminant, convergent, and criterion validity. Together, these findings indicate that our theory driven model of sense of community in the school is valid and that the instrument is a reliable measure for assessing sense of community in the school.